The Effectiveness of Probiotics to Increase the Growth of Freshwater Barramundi (Lates Calcarifer) Seeds - Ranim, Yenfi Riza; Salamah, Salamah; Rusydi, Rachmawati; Mahdaliana, Mahdaliana; Mainisa, Mainisa (Jurnal Ilmiah Samudra Akuatika, 2022)
This study aims to determine the effect of the effectiveness of giving probiotic for increasing the growth and digestibility of freshwater barramundi seed feed. The research was conducted on January 29 - February 28 2022 at the Kembang Tani Farm Lancang Barat Hacthery, North Aceh. The experimental research method used a non-factorial Completely Randomized Design (CRD) with 4 treatments with 3 replications, namely Treatment A: Probiotic EM4 0 ml/kg feed, Treatment B: 9 ml/kg feed, Treatment C 12 ml/kg feed and Treatment D: 15 ml/kg feed. The best length gain was found in treatment D 2.36 cm. The best weight gain in treatment D was 1.91 grams. The best FCR in treatment D 1.5. Best survival in treatment D 86.67%.